2010
DOI: 10.1007/s12149-010-0448-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of anatomical normalization errors in SPM and 3D-SSP using digital brain phantom

Abstract: When required to evaluate regions with decreased perfusion due to such causes as hemodynamic cerebral ischemia, the 3D-SSP is desirable. In a statistical image analysis, we must reconfirm the image after anatomical standardization by all means.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…To minimize the deviation errors caused by analysis software packages, 3D-SSP and eZIP image-processing programs were applied in the same CT attenuation-corrected SPECT images data of MDD patients and normal controls. According to previous studies [ 24 , 25 ], the difference between 3D-SSP and eZIP lies in smoothing process after anatomic standardization. The smoothing process by eZIP is based on an SPM algorithm and effectively enhances the signal-noise ratio of images, which might overestimate cerebral hypoperfusion [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To minimize the deviation errors caused by analysis software packages, 3D-SSP and eZIP image-processing programs were applied in the same CT attenuation-corrected SPECT images data of MDD patients and normal controls. According to previous studies [ 24 , 25 ], the difference between 3D-SSP and eZIP lies in smoothing process after anatomic standardization. The smoothing process by eZIP is based on an SPM algorithm and effectively enhances the signal-noise ratio of images, which might overestimate cerebral hypoperfusion [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies [ 24 , 25 ], the difference between 3D-SSP and eZIP lies in smoothing process after anatomic standardization. The smoothing process by eZIP is based on an SPM algorithm and effectively enhances the signal-noise ratio of images, which might overestimate cerebral hypoperfusion [ 24 , 25 ]. So we apply corrections for multiple comparisons based on family-wise error (FEW), and P FWE-corr < 0.05 is considered statistically significant in eZIP analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Another problem with Method 2 is the possible creation of errors by misregistration of amyloid images. While the reason for this is not clear, it has been reported that standardization by 3D-SSP was not accurate enough at a head tilt of approximately 25°or more [20]. It is thus important to check each image after registration and AS.…”
Section: Discussionmentioning
confidence: 99%
“…All SPECT images were analyzed using AZE Virtual Place HAYABUSA software (Canon Medical Systems), and 3-dimensional stereotactic surface projection analysis was performed. To avoid anatomic standardization errors, the head tilt was adjusted to the anterior commissure-posterior commissure line (19,20). Counts of 37 brain regions were measured using volume-of-interest templates incorporated into the 3-dimensional stereotactic surface projection on anatomically standardized SPECT images.…”
Section: Discussionmentioning
confidence: 99%